The Dark Ghetto revisited: Kenneth B Clark's classic analysis as cutting edge criminology. (February 2015) - Currie, Elliott; Goddard, Tim; Myers, Randolph R
In this article we revisit one of the classic works of the 1960s on crime and delinquency in poor communities: Kenneth B Clark's Dark Ghetto . Our exploration reveals its insights to be extremely relevant today both in understanding the roots of the self-destructive violence that tears at those communities and in thinking about how to combat the structural conditions and individual mentalities that generate it. Beyond the specific theoretical and methodological lessons that can be gleaned from Dark Ghetto, Clark's work serves as a much-needed illustration of how theoretical insights derived from intensive qualitative research that is attuned to political, historical, and economic realities—and their human consequences—can enhance criminological theory, and align with progressive movements for social change.